The Influence Of The Safety Management System (Sms) And The Role Of Organizations On Aviation Safety Through Safety Culture At XYZ Airport - Muhammad Koharudin; Prasadja Ricardianto; Euis Saribanon; Salahudin Rafi (Dinasti Publisher, 2025)
This research is motivated by increased incidents in 2023 compared to 2022, an occurrence from the Airport Safety Performance Indicators where the highest criteria for incidents in 2019 - 2023 are Bird Strikes (bird attacks) with 3 (three) incidents. This research aims to determine the influence of the Safety Management System (SMS) and the role of organizations on aviation safety through the safety culture at XYZ Airport. The research method is quantitative. The sample used was 250 respondents who were PT Angkasa Pura II employees at XYZ Airport. The sampling technique uses a simple random sampling technique. The data collection technique is a questionnaire. The data analysis technique uses Structural Equation Modeling (SEM) based on Smart PLS 2024. The research results show that safety culture can be influenced by the implementation of the safety management system and the role of the organization, aviation safety is not influenced by the role of the organization but is influenced by the implementation of the safety management system and safety culture, the implementation of the safety management system does not affect aviation safety through safety culture, and the role of the organization can influence aviation safety through safety culture. Researchers hope that companies will continue to carry out evaluations and innovations to improve security system management.